Examining the relationship between selected risks with profitability performance of foreign-owned Islamic Bank in Malaysia: a study of Standard Chartered Saadiq Berhad / Nur Syafiqah Abdullah - Abdullah, Nur Syafiqah (Faculty of Business and Management, 2018)
Most of financial institution systems have been affected due to global financial crisis in 2008 in which consequently caused the financial institutions to be exposed with risks. This project paper focused on how profitability performance of banks can be influenced by the presence of selected risks. The aim of this study is to examine the relationship and impacts of credit risk (CR), market risk (MR), liquidity risk (LR) and operational risk (OPR) with return on assets (ROA) of foreign-owned Islamic Bank in Malaysia. In Malaysian context, this study is an extension from previous study by combining all the risks while focusing on foreign-owned Islamic Bank in order to study about the concept of risk and return. This study utilized quarterly data collected from financial reports of Standard Chartered Saadiq Berhad in Malaysia over the period of December 2008 – June 2017. Ordinary Least Square (OLS) method is used in this study in order to do the empirical analysis using eviews software. The findings revealed that there is positive significant relationship between OPR and ROA of Standard Chartered Saadiq Berhad in Malaysia. However, CR and MR are found positive and insignificant towards ROA while LR is found negative insignificant on ROA. The study of risks impact on foreign-owned Islamic Bank in Malaysia can provide the empirical literature for future research. This study enhanced the bank regulators and policymakers to have better risk management to sustain the profitability performance of the bank.